Stones and the Destabilisation of Safe Ethical Space - Eriksen, Helen; Ulrichsen, Gry O.; Bayati, Zahra (Periskop – Forum for kunsthistorisk debat, 2020)
This article investigates the role of ethical boundaries for the academic and the artist/researcher in stabilising or destabilising colonialised positions of power. It stems from an increasingly urgent need to understand how the exclusion of pluralistic knowledge production continues in professional contexts and how this supports supremacist structural power imbalances.